Stability Analysis of Finger Millet Genotypes Across Diverse Hilly and Mountainous Environments in Nepal - Manoj Kandel; Bishnu Prasad Kandel; Madhu Sudhan Ghimire; Arjun Bastola; Puruswattam Bahadur Runiyar (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
The interactive influence of the genotype and environment (GxE) affects the selection criteria of fingermillet (Eleusine coracana L.) genotypes. Sixteen fingermillet genotypes are evaluated for stability of grain yield performance in three hilly and mountainous environments viz Dolakha, Ramechhap, and Sindupalchowk in rainy seasonsof 2019. This study intends to determine the interaction between genotype and environment on growth and yield performance of fingermillet genotypes. The results show that there are significant differences between the genotypes for grain yield. The pooled analysis show significant (p<0.05) variation in GxE interaction for grain yield. The genotypes GE-0382, KLE-216, NE-94, and KLE-559 are found environmentally sensitive, producing higher grain yield throughout the environments. Genotypes GE-0382 and KLE-559 have the regression coefficient of 1.30 and 1.35, respectively. The coefficient of determination (R2) for genotypes viz GE-0382 and KLE-559 are high as 0.9, confirming their high constancy for the solidity across the different locations. Further GGE biplot analysis reveals that the genotype GE-0382 (3.46 t/ha) and KLE-559 (2.74 t/ha) are more secure and adaptable genotypes over the tested environment. Thus, these genotypes presumably are used to develop suitable finger millet varieties for general cultivation across the mid-hill environment of Nepal.